Out-of-pocket payment for surgery in uganda - Anderson, Geoffrey A; Ilcisin, Lenka; Kayima, Peter; Abesiga, Lenard; Benitez, Noralis Portal; Ngonzi, Joseph; Ronald, Mayanja; Shrime, Mark G (PLOS ONE, 2017)
Background and objectives It is Ugandan governmental policy that all surgical care delivered at government hospitals in Uganda is to be provided to patients free of charge. In practice,however, frequent stock outs and broken equipment require patients to pay for large portions of their care out of their own pocket. The purpose of this study was to determine the financial impact on patients who undergo surgery at a government hospital in Uganda. Methods Every surgical patient discharged from a surgical ward at a large regional referral hospital in rural southwestern Uganda over a 3-week period in April 2016 was asked to participate. Patients who agreed were surveyed to determine their baseline level of poverty and to assess the financial impact of the hospitalization. Rates of impoverishment and catastrophic expenditure were then calculated. An “impoverishing expense” is defined as one that pushes a household below published poverty thresholds. A “catastrophic expense” was incurred if the patient spent more than 10% of their average annual expenditures. Results We interviewed 295 out of a possible 320 patients during the study period. 46% (CI 40– 52%) of our patients met the World Bank’s definition of extreme poverty ($1.90/person/day). After receiving surgical care an additional 10 patients faced extreme poverty, and 5 patients were newly impoverished by the World Bank’s definition ($3.10/person/day). 31% of patients faced a catastrophic expenditure of more than 10% of their estimated total yearly expenses. 53% of the households in our study had to borrow money to pay for care, 21% had to sell possessions, and 17% lost a job as a result of the patient’s hospitalization. Only 5% of our patients received some form of charity. Conclusions and relevance Despite the government’s policy to provide “free care,” undergoing an operation at a government hospital in Uganda can result in a severe economic burden to patients and their families. Alternative financing schemes to provide financial protection are critically needed.
The rate of impoverishing and catastrophic expenditure at a government hospital